Penegakan Hukum Pidana Terhadap Peredaran Rokok Ilegal Oleh Penyidik Bea dan Cukai - Nanda, Nanda Nugraha Ziar; M. Musa (Desiderata Law Review, 2024)
What triggers smuggling is technological advances that make international business/trade relations easier to access. Customs and Excise classifies Illegal Cigarettes smuggling into several groups. With the smuggling of illegal cigarettes, the circulation of illegal cigarettes is quite worrying because they are widely circulated and traded in a number of shops, supermarkets and stalls in most areas of Tembilahan City. In order to carry out the supervisory function of the means of transportation, the customs and excise officials are given the authority to be able to inspect the means of import. As for this research, there is a main problem that will be discussed, namely, How to Implement Criminal Law Enforcement Against Investigation of Illegal Cigarette Circulation by the Tembilahan Customs and Excise Regional Office. And the purpose of this research is to find out the criminal law enforcement process for illegal cigarette distribution at the Tembilahan Customs and Excise Regional Office. In this case, the researcher uses an empirical juridical approach in analyzing the problem by combining legal materials (secondary data) with primary data obtained in the field, namely about the role of Customs and Excise in Overcoming the Problem of Illegal Cigarette Circulation. The results of the research that the authors obtained were the implementation of the duties and authorities of the Customs and Excise of the City of Tembilahan in taking action against the criminal act of smuggling of illegal cigarettes in the City of Tembilahan, namely by carrying out an oversight of goods entering from outside the area.